Exploring and reviewing tools to evaluate midwifery students' clinical education perceptions and impact - Gita Indri Puspitawanti (Universitas Pendidikan Indonesia, 2025)
This study aims to evaluate midwifery students’ perceptions of their clinical learning environment and its impact on clinical learning outcomes. The study is grounded in the importance of a supportive clinical environment to optimize students’ competency achievement. A literature review method was employed by examining recent international journal articles accessed through Google Scholar and PubMed. The reviewed articles discuss clinical education evaluation tools, students’ perceptions of clinical learning settings, and the relationship between these perceptions and clinical learning outcomes. The findings reveal that positive student perceptions of the clinical environment are significantly associated with improved learning outcomes, including enhanced practical skills and increased motivation. Furthermore, the quality of the clinical learning environment can be improved through the use of better evaluation instruments, tutor training, and the strengthening of clinical facilities. This study highlights the importance of continuous monitoring and quality improvement in midwifery clinical education to ensure that graduates are competent and ready for professional practice. The results provide valuable insights for midwifery education institutions to design effective strategies that enhance clinical learning environments and reinforce student learning outcomes. Abstrak Studi ini bertujuan untuk mengevaluasi persepsi mahasiswa kebidanan terhadap lingkungan belajar klinik serta dampaknya terhadap hasil belajar klinik. Latar belakang studi ini didasarkan pada pentingnya lingkungan belajar klinik yang kondusif dalam mendukung pencapaian kompetensi mahasiswa secara optimal. Penelitian ini menggunakan metode tinjauan literatur dengan menelaah artikel jurnal internasional terkini yang diakses melalui Google Scholar dan PubMed. Artikel yang dikaji membahas alat evaluasi pendidikan klinik, persepsi mahasiswa terhadap lingkungan belajar klinik, serta hubungan antara persepsi tersebut dengan hasil belajar klinik. Hasil kajian menunjukkan bahwa persepsi positif mahasiswa terhadap lingkungan klinik secara signifikan berkaitan dengan peningkatan hasil belajar, termasuk keterampilan praktik dan motivasi belajar. Selain itu, peningkatan kualitas lingkungan belajar klinik dapat dicapai melalui perbaikan instrumen evaluasi, pelatihan tutor, serta penguatan sarana dan prasarana klinik. Studi ini menegaskan pentingnya pemantauan dan peningkatan berkelanjutan dalam pendidikan klinik kebidanan untuk menjamin lulusan yang kompeten dan siap menghadapi dunia kerja profesional. Temuan ini memberikan masukan penting bagi institusi pendidikan kebidanan dalam merancang strategi untuk meningkatkan kualitas lingkungan belajar klinik dan memperkuat hasil belajar mahasiswa. Kata Kunci: evaluasi pendidikan kebidanan; penilaian mahasiswa; persepsi mahasiswa